Overcoming Barriers in Antenatal Care Visits: Challenges and Solutions for Improved Maternal Health - Sundas Gul, Neelam Abbas, Misbah Harim, Nazma Gul, Amna Begum, Afshan Jehan Zeb (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Antenatal care (ANC) is critical for ensuring maternal and fetal health, yet adherence remains suboptimal in many low-resource settings. This study aimed to identify barriers to ANC visits and propose strategies to improve adherence among pregnant women. Methodology: A cross-sectional study was conducted among 422 pregnant women attending a tertiary care facility from August 2022 to August 2023 at Khyber Teaching Hospital Peshawar. Participants were selected through consecutive sampling and data were collected using structured questionnaires. Barriers to ANC were categorized into logistical, financial, cultural, and healthcare system-related factors. Statistical analyses included chi-square tests and logistic regression to identify predictors of ANC adherence. Results: 38.6% of the population attended all eight of their recommended ANC visits. Big concerns were issues with logistics (76.2%), money challenges (63.4%), and cultural variances (48.9%). Living in a remote region, having few education, and having a lower socioeconomic level were associated with poor adherence (p<0.05p<0.05). Strong predictors of adherence, according a multivariate study, were living in a city and education (OR=2.45 and OR=2.71 respectively). Conclusion: Though there are several reasons why people find it difficult to follow ANC, the primary ones are cultural, financial, and practical ones. To raise ANC attendance and mothers’ health, focused interventions including free or low-cost transportation, educational initiatives, and programs involving men participation are required. Keywords: Antenatal care, maternal health, barriers, adherence, rural healthcare, socioeconomic factors